A Rare Case of Metastatic Primary Peritoneal Ependymoma: A Case Report and Literature Review - Ben Man Fei Cheung; Johnny Kin Sang Lau; Anthony W. I. Lo; Mai-Yee Luk; Kwok Keung Yuen (Case Reports in Oncological Medicine)
Background. Primary peritoneal ependymoma is an exceedingly rare tumour with only four cases reported in the literature. It typically follows an indolent disease course. We describe a rare case of metastatic primary peritoneal ependymoma which was treated with chemotherapy and radiotherapy resulting in prolonged survival to date for 10 years. Case Presentation. The patient was a 23-year-old female on presentation. She presented with right upper quadrant pain associated with an abdominal mass. Computed tomography demonstrated a large mass displacing the liver. Debulking surgery was done revealing a tumour arising from the peritoneum as well as multiple metastatic pleural and peritoneal nodules. Pathology was consistent with primary peritoneal ependymoma. The patient was then treated with multiple lines of chemotherapy containing etoposide as the backbone. She also received palliative radiotherapy to the thoracic metastases with good and durable response. Conclusion. We reported a rare case of metastatic primary peritoneal ependymoma. Etoposide containing the chemotherapy regimen is effective in the treatment of peritoneal ependymoma. Radiotherapy is also effective for palliation of local symptoms with durable response.